DETEKSI SENYAWA METABOLIT SEKUNDER JAMUR ENDOFIT DARI AKAR TANAMAN KARET (Hevea brasiliensis) - Widya Lestari (UNIVERSITAS LABUHANBATU, 2014)
Endophytic fungi are a group of fungi whose part or whole life is in living plant tissue and usually does not harm the host. Endophytic fungi generally produce secondary metabolites that have beneficial biological activities such as anti-cancer compounds, antifungi or antibacterials. Control of plant diseases caused by Rigidoporus microporus and Ganoderma boninense can be done by using biological agents, namely by using endophytic fungi. This fungus has metabolite compounds that can inhibit the growth of Rigidoporus microporus and Ganoderma boninense. This study aims to determine what content is found in endophytic mushroom extracts isolated from rubber plants (Hevea brasiliensis). Endophytic fungi are extracted by maceration using methanol and ethyl acetate solvents. The extract was tested for antifungal activity using diffusion method. The content of secondary metabolites was tested by phytochemical test. The results of endophytic fungal extraction with methanol and ethyl acetate solvents resulted in antifungal activity with inhibitory zones in a row namely WL01: 2.19 and 2.15 mm Fungi Isolates on Ganoderma boninense while 3.09 mm WL02 against Rigidoporus microporus Based on the phytochemical test results, endophytic fungal extract with methanol and ethyl acetate solvents showed the presence of alkaloid, flavonoid, phenol and saponin. Keywords: endofit, fungi, hevea, secondary metabolites